2016
DOI: 10.15360/1813-9779-2016-4-37-48
|View full text |Cite
|
Sign up to set email alerts
|

Phenylcarboxylic Acids in The Assessment of The Severity of Patient Condition and The Efficiency of Intensive Treatment in Critical Care Medicine

Abstract: Разработка точных и практичных методов оценки тяжести состояния больных является важной задачей в анестезиологии реаниматологии.Цель работы -обосновать целесообразность измерения фенилкарбоновых кислот (ФКК) в крови для оценки тяжести состояния и эффективности лечения больных в отделении реаниматологии.Материалы и методы. В день поступления в отделение реаниматологии и в динамике у больных с ост рыми хирургическими заболеваниями органов брюшной полости (n=58) регистрировали объективные кли нико лабораторные по… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…At the same time, the summary levels of microbial metabolites in the serum samples were higher for the ACI patients. Earlier, we have shown that the sum of three AMM (p-HPhAA, p-HPhLA, PhLA) reflects the severity of disease in patients admitted to ICU as good as conventional scales APACHE II and SOFA [32,39] and their concentrations increased in dynamics in non-survived patients [26], due to their production by pathobionts, such as Staphylococcus aureus, Klebsiella pneumonia, Acinetobacter baumanii, Pseudomonas aeruginosa, and Escherichia coli [40,41].…”
Section: Discussionmentioning
confidence: 95%
“…At the same time, the summary levels of microbial metabolites in the serum samples were higher for the ACI patients. Earlier, we have shown that the sum of three AMM (p-HPhAA, p-HPhLA, PhLA) reflects the severity of disease in patients admitted to ICU as good as conventional scales APACHE II and SOFA [32,39] and their concentrations increased in dynamics in non-survived patients [26], due to their production by pathobionts, such as Staphylococcus aureus, Klebsiella pneumonia, Acinetobacter baumanii, Pseudomonas aeruginosa, and Escherichia coli [40,41].…”
Section: Discussionmentioning
confidence: 95%
“…[25,26]. The highest levels of these PhCAs are detected in the serum of patients with multiple organ dysfunction syndrome in sepsis [26,27,28]. These metabolites can come from both sources: the local focus of infection and intestinal bacteria [26,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Critical conditions are known to be accompanied by intestinal failure, which leads to a reduction in bacterial diversity and an accumulation of mostly gram-negative microorganisms, which are the main producers of the PhCAs [31]. The sum of three PhCAs reflects the disease severity as do the conventional scales Acute Physiology and Chronic Health Evaluation II (APACHE II) and Sequential (Sepsis-related) Organ Failure Assessment (SOFA) [27,28]. The PhCA concentrations are demonstrated to increase in dynamics in non-survived patients while they decrease gradually in critical surviving patients [32].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the AMM level relects the severity of the infectious process and is directly correlated with the number of clinical signs of inlammation, indicators of severity APACHEII and SOFA scores [24].…”
Section: Bacterial Load and Neutrophilsmentioning
confidence: 99%